The life and times of Judge Roy Bean [videorecording (DVD)] - Huston, John, 1906-1987; Newman, Paul, 1925-2008; Bisset, Jacqueline, 1944-; Hunter, Tab, 1931-2018; Keach, Stacy; McDowall, Roddy; Perkins, Anthony, 1932-1992; Gardner, Ava, 1922-1990 (Warner Home Video, 2003)
Roy Bean is a self-made man and saloon-keeper who proclaims himself the law west of the Pecos River, and becomes known as the "Hanging Judge," though he wasn't a judge at all. He writes admiring letters to actress Lily Langtry and makes his own kind of frontier justice in Texas.